Cost-effectiveness of Sativex in multiple sclerosis spasticity: new data and application to Italy. (June 2015) - Slof, John; Ruiz, Leonardo; Vila, Carlos
<x xml:space="preserve">Abstract</x> Multiple sclerosis (MS) is a chronic progressive disease that carries a high socioeconomic burden. Spasticity (rigidity and spasms) is common in MS and contributes to MS-related disability. This study aims to evaluate the cost–effectiveness of Sativex® (9-delta-tetrahydrocannabinol plus cannabidiol oromucosal spray) when used as add-on therapy for management of resistant MS-related spasticity in the context of the Italian healthcare system. A previously published Markov model-based analysis for the German and Spanish context was replicated, adapting it to the Italian setting. Model parameters were updated to reflect recent findings about MS-related spasticity and use of Sativex in daily clinical practice. The base case incremental cost–effectiveness ratio for Sativex use in Italy over a 5-year period was estimated to be €4968 per quality-adjusted life-year gained (year of costing: 2013). Sativex remained an efficient option in the Italian healthcare context – below the commonly accepted incremental threshold of €30, 000 per quality-adjusted life-year gained – when deterministic and probabilistic sensitivity analyses were conducted. Sativex can be regarded as a cost-effective treatment option for patients with MS-related spasticity in Italy.